PENERAPAN POWERPOINT INTERAKTIF DALAM MENGEMBANGKAN KOSAKATA BAHASA INGGRIS ANAK (PENELITIAN DESKRIPTIF TERHADAP ANAK USIA 5-6 TAHUN DI RA BANY RADHIYYA BANJARAN KABUPATEN BANDUNG TAHUN AJARAN 2021-2022) - Intan Permanik (Lembaga P3M, 2022)
This study aims to describe deeply about the implementation of powerpoint in developing English vocabulary which was conducted in early childhood education. One of the characteristics of early childhood is ‘hands on experience’ learner, so interactive powerpoint can adjust to this characteristic. This study uses Thematic analysis in which refers to the research questions that become basic themes to analyze. The data collection tools are observation (field note and interview guide), interview and documentation. The findings show that the implementation of powerpoint was conducted in accordance with daily implementation plan or RPP that applied in RA Bany Radhiyya. Moreover, the vocabulary given is being associated with thematic theme: 'my home' theme with sub submues: ‘Part of House' and ‘Kitchen Utensils